2012
DOI: 10.1186/1756-9966-31-79
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Direct sequencing, Pyrosequencing, High resolution melting analysis, TheraScreen DxS, and the K-ras StripAssay for detecting KRAS mutations in non small cell lung carcinomas

Abstract: BackgroundIt is mandatory to confirm the absence of mutations in the KRAS gene before treating metastatic colorectal cancers with epidermal growth factor receptor inhibitors, and similar regulations are being considered for non-small cell lung carcinomas (NSCLC) and other tumor types. Routine diagnosis of KRAS mutations in NSCLC is challenging because of compromised quantity and quality of biological material. Although there are several methods available for detecting mutations in KRAS, there is little compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 37 publications
4
51
0
1
Order By: Relevance
“…Moreover, RFLP and ARMS assays are required for confirmation testing (14). Although the DNA sequencing technique is widely recognized as the gold standard for screening genomic variations, its widespread use is hampered by its cost-and time-consuming nature (15).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RFLP and ARMS assays are required for confirmation testing (14). Although the DNA sequencing technique is widely recognized as the gold standard for screening genomic variations, its widespread use is hampered by its cost-and time-consuming nature (15).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past five years, several new techniques, including peptide-nucleic-acid-mediated polymerase chain reaction clamping (PNA-PCR), have emerged. These methods have higher sensitivity than direct sequencing, and permit the detection of lower mutation frequencies (1%-5%) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In tumors with little mutant DNA present, this will lead to differences in mutation detection. Similar small differences between methods using Therascreen as a comparator have been reported by others [18,[24][25][26][27][28][29]. Chang et al [23] conducted a retrospective study of the CRYS-TAL trial samples with Therasceen and LNA, showing excellent concordance, while Gonzalez de Castro et al [18] showed similarly good concordance of 98% between Therascreen and cobas (Roche).…”
Section: Discussionmentioning
confidence: 63%
“…Altimari et al [27] showed reasonable concordance between Therascreen, pyrosequencing and Roche 454 sequencing, but noted the poor diagnostic sensitivity of Sanger sequencing. Therascreen has also been used to validate other PCR assays [25,28], including high resolution melt analysis [29]. It should be noted that the diagnostic sensitivity of sequencing methods is dependent on the size of PCR products: FFPE tissue samples have fragmentation of their DNA and products > 150 bp suffer loss of diagnostic sensitivity [30].…”
Section: Discussionmentioning
confidence: 99%